Structural impact simulation using program Krash - Liaw, J. C. (Cranfield University, 1992)
Use is made of the KRASH program to simulate a simplified car-into-barrier impact. A step-by-step modelling technique is illustrated whose application at an early stage in the design process, allows an understanding of the contribution of individual components to the overall crash-performance of a vehicle.

Use is made of the KRASH program to simulate a simplified car-into-barrier impact. A step-by-step modelling technique is illustrated whose application at an early stage in the design process, allows an understanding of the contribution of individual components to the overall crash-performance of a vehicle.

This report is a summary of the group design project of the MSc in Astronautics and Space Engineering at Cranfield University for the year 1996/97. The project was a feasibility study of a European unmanned mission to the lunar south pole to carry out scientific study. The mission proposed uses two spacecraft: (1) an orbiter to take images of the proposed landing site, to measure the Moon’s gravitational field, and to act as a communications relay, and (2) a larger lander which carries a small rover and a crate probe. The orbiter is launched first (if gravity and image data are not already available) so that the lander’s landing site can be selected. The main goal is scientific study of the permanently dark craters at the lunar south pole. The baseline design (developed to the depth of a feasibility study) meets the stated requirements and is comparable to ESA’s medium class missions (cost € 300 M).